Examining the Impact of a Nurse Navigator Program on Anxiety, Psychological Well-being, and Quality of Life in Breast Cancer Patients at a Tertiary Care Hospital in Haryana: A Randomized Controlled Trial - Kavita Choudhary; Nityasha Dalal (International Journal of Oncological Nursing and Practices, 2024)
Background of study: Breast cancer stands as the leading cancer type affecting women and remains a significant contributor to female mortality. It is a complex ailment influenced by multiple factors. Globally, in 2020, approximately 2.3 million women received diagnoses of breast cancer, resulting in 685,000 fatalities. This condition can profoundly impact various aspects of a person's existence, encompassing physical, psychological, emotional, social, and familial spheres. A notable observation is the heightened psychological distress experienced by a majority of women afflicted with breast cancer. Objectives: (i) The primary objective was to gauge the levels of anxiety, psychological distress, and quality of life among breast cancer patients who have undergone surgery and subsequent adjuvant chemotherapy. (ii) Additionally, the aim was to assess the impact of a nurse navigator program on anxiety, psychological distress, and quality of life experienced by breast cancer patients. Methodology: The research employed a randomized controlled trial methodology, wherein individuals were assigned randomly to either the intervention or control group, each consisting of 60 participants. Various assessment instruments were utilized for data gathering, such as a baseline proforma, Depression, Anxiety and Stress Scale–21 (DASS 21), and the Functional Assessment of Cancer Therapy–Breast (FACT-B) instrument. Results: The results revealed that the average age of participants in the intervention group was 46.222 ± 8.47 years, whereas in the control group, it averaged at 45.22 ± 9.22 years. Analysis of the intervention's impact on outcome variables demonstrated statistically significant reductions in mean anxiety scores, as evidenced by repeated analysis of variance (F (df 1,118) = 12984.191, p = .000) and within-group analysis (F (df 4, 1.314) = 408,964, p = .000), as well as decreases in depression scores (between groups F (df 1, 118) = 8920.942, p = .000; within-group F (df 4, 1.644) = 109.247, p = .000), and stress scores (between groups F (df 1, 118) = 1158.535, p = .000; within-group F (df 4, 1.214) = 36.244, p = .000). Moreover, there was a significant improvement in quality-of-life scores, particularly in the Physical Well-Being domain, compared to the control group (between the groups F (df 1, 118) = 6847, p = .000; within-group F (df 4, 2,037) = 1321, p = .000). Consequently, it was concluded that the Nurse Navigator Program effectively reduced anxiety and psychological distress while enhancing the quality of life among breast cancer patients. Conclusion: The analysis findings show that the Nurse Navigator Program was effective in relieving anxiety, psychological distress and improving quality of life among breast cancer patients undergoing surgery followed by chemotherapy.
Keywords: Anxiety; Nurse Navigator Program; Quality of life; adjuvant therapy; breast cancer; nursing intervention; psychological distress